Anthocyanins from Mauve Flowers of Erlangea tomentosa (Bothriocline longipes) Based on erlangidin – The first Reported Natural Anthocyanidin with C-ring methoxylation - Adaku, Christopher; Skaar, Irene; Berland, Helge; Byamukama, Robert; Jordheim, Monica; Andersen, Øyvind M. (Phytochemistry Letters, 2019)
Above 700 different anthocyanins have been isolated from plants. These flavonoid pigments are grouped after the number and position of hydroxy- and methoxy-groups on their anthocyanidin A- and B-rings, which influence their properties. In this study two new anthocyanins, erlangidin 5-O-(4″-(E-caffeoyl)-6″-(malonyl)-β-glucopyranoside)- 3′-O-(6‴-(3II-(β-glucopyranosyl)-E-caffeoyl)-β-glucopyranoside) and erlangidin 5-O-(6″-(malonyl)- β-glucopyranoside)-3′-O-(6‴-(3II-(β-glucopyranosyl)-E-caffeoyl)-β-glucopyranoside) were isolated from purple flowers of Erlangea tomentosa (Bothriocline longipes) Oliv. & Hiern (Asteraceae) in amounts of ∼1.6 and 0.6 mg/g fr. wt., respectively. They were found to contain the first reported natural anthocyanidin with a methoxy-group on the heterocyclic C-ring, which we have given the name erlangidin.” During extraction, isolation and storage in acidified methanolic solvents the two anthocyanins were both partly converted to their demalonylated and methylmalonyl esterified forms. Spectroscopic and chromatographic characteristics for erlangidin in comparison with the common anthocyanidins, which it might be mistaken for, are included.
Keywords: Erlangea tomentosa; Bothriocline longipes; Compositae; Anthocyanins; Erlangidin; Analytical characteristics